Mejora de las Operaciones Logísticas Administrativas en la IPS Oncológica a Través del uso De Herramientas Lean Healthcare (2022)
Abstract— Facing the need to improve the administrative operations within the organizations providing health services, the initial phase of implementation of Lean Healthcare is shared, to optimize processes by eliminating activities that do not provide added value and decrease quality. The main focus of the project was to generate a process of continuous improvement in the administrative functions of the Oncological IPS through the 9’s, Amfe, and Vsm methodology, to increase the satisfaction and importance of the users and the quality of the service. Initially, a diagnosis of the current situation was carried out, identifying the critical variables, applying the tools from the short-term solution strategies, validating them through an analysis of management indicators.   As a result, a matrix of management indicators was proposed, eight of which are fully proposed to evaluate the impact of the project, in which greater participation of the members was obtained, seventeen application documents were generated from the strategies developed, where twenty of the twenty-eight critical factors identified were solved, increasing efficiency in daily activities, productivity, and performance of workers.